Coordinated elevation of membrane type 1-matrix metalloproteinase and matrix metalloproteinase-2 expression in rat uterus during postpartum involution - Kanaya Mika; Goto Taeko; Kitajima Yoshimitu; Yamazaki Kiyohiro; Honnma Hiroyuki; Nagasawa Kunihiko; Chida Mitunobu; Endo Toshiaki; Manase Kengo; Hayashi Takuhiro; Mitaka Toshihiro; Saito Tsuyoshi (BMC, 2006)
Abstract Background The changes occurring in the rodent uterus after parturition can be used as a model of extensive tissue remodeling. As the uterus returns to its prepregnancy state, the involuting uterus undergoes a rapid reduction in size primarily due to the degradation of the extracellular matrix, particularly collagen. Membrane type-I matrix metalloproteinase (MT1-MMP) is one of the major proteinases that degrades collagen and is the most abundant MMP form in the uterus. Matrix metalloproteinase-2(MMP-2) can degrade type I collagen, although its main function is to degrade type IV collagen found in the basement membrane. To understand the expression patterns of matrix metalloproteinases (MMPs) in the rat uterus, we analyzed their activities in postpartum uterine involution. Methods We performed gelatin zymography, northern blot analysis and immunohistochemistry to compare the expression levels of MT1-MMP, MMP-2, matrix metalloproteinase-9 (MMP-9) and the tissue inhibitors of MMPs-1 and 2 (TIMP-1 and TIMP-2) in the rat uterus 18 h, 36 h and 5 days after parturition with their expression levels during pregnancy (day 20). Results We found that both MT1-MMP and MMP-2 localized mainly in the cytoplasm of uterine interstitial cells. The expression levels of MT1-MMP and MMP-2 mRNAs and the catalytic activities of the expressed proteins significantly increased 18 h and 36 h after parturition, but at postpartum day 5, their mRNA expression levels and catalytic activities decreased markedly. The expression levels of MMP-9 increased 18 h and 36 h after parturition as determined by gelatin zymography including the expression levels of TIMP-1 and TIMP-2. Conclusion These expression patterns indicate that MT1-MMP, MMP-2, MMP-9, TIMP-1 and TIMP-2 may play key roles in uterine postpartum involution and subsequent functional regenerative processes.